The Creativity of the Reporting in the Rhetorical Text - Ezzat, Azza Adnan Ahmed (Arab Journal for Sciences and Research Publishing, 2019)
Every Qur'anic surah has a different specificity than others, Surat Al-Takwer deals with two facts of the doctrine in two parts: the first starts with the early begging of the verse and ends of verses (1-14), which talks about the Doomsday and the accompanying of a massive universe reduction and the fall of all the surroundings things and entities. What observe is that the long-open syllable (C V V) only accounted for (8.06%) of the syllables, while the ratio of short-open syllable (C V) was above (56.45%), and the percentage of the short –closed syllable (C VC) touched (35.48%). All these portrayed with what looks like accompanied music, the agility of the drastic scene and the enormous revolution that turns everything upside down and spread it,so it aggravates the stable and torments helpless people with its rapid rhythm. The second part starts of verses (15-29), and it confirms the sincerity of the Prophet (peace and blessings of Allaah be upon him) in the reporting of his Lord, and shows that the Qur'an was sent to be a guide and an admonition to the whole world until the Judgment Day.We found that the ending intervals in the first four verses that address the truth of the afflatus and the role of the Prophet (peace and blessings of Allaah be upon him), and the characteristics of the addressed people end up in the closed syllable (CVC) with the explosive voice of (S) which is voiceless alveolar fricative with a whistling lighter and less intensive than the extreme explosive (t) sound which is used in the intervals of the verses of the first part to fit the situation. In the other hand, the last verses ended with the long closed Syllable (CVVC) with the sound (M) and , preceded by two voiced and mild (Ya) and (Waw) and they have a harmony with the third situation: the persuasion of following the Prophet (peace and blessings of Allaah be upon him), the Qur'an and revelation, which have a harmony with the decline of strong sounds from (24%) In the first part to (20%) In the second part. The effect of the rhythm was evident in terms of the lexical level, or morphological level or in terms of grammatical compositions as well as the qualities and the outlets of its sounds were obvious. Then it became apparent that the rhythm of the used voiced and the voiceless sounds in the syllables (opened or closed; short or long) was significant. In addition it is doubtless that the morphemic forms (bases or derived, passive or active) have a semantic and vocal effect, especially in the various Qur'anic readings.
Keywords: Sound; syllable, vowels; consonants; meaning; context; rhythm; music